34.3.9 problem 10

Internal problem ID [6048]
Book : A treatise on ordinary and partial differential equations by William Woolsey Johnson. 1913
Section : Chapter VII, Solutions in series. Examples XIV. page 177
Problem number : 10
Date solved : Monday, January 27, 2025 at 01:34:24 PM
CAS classification : [[_2nd_order, _with_linear_symmetries]]

\begin{align*} \left (4 x^{3}-14 x^{2}-2 x \right ) y^{\prime \prime }-\left (6 x^{2}-7 x +1\right ) y^{\prime }+\left (6 x -1\right ) y&=0 \end{align*}

Using series method with expansion around

\begin{align*} 0 \end{align*}

Solution by Maple

Time used: 0.007 (sec). Leaf size: 28

Order:=6; 
dsolve((4*x^3-14*x^2-2*x)*diff(y(x),x$2)-(6*x^2-7*x+1)*diff(y(x),x)+(6*x-1)*y(x)=0,y(x),type='series',x=0);
 
\[ y = c_1 \sqrt {x}\, \left (1+2 x +\operatorname {O}\left (x^{6}\right )\right )+c_2 \left (1-x +\operatorname {O}\left (x^{6}\right )\right ) \]

Solution by Mathematica

Time used: 0.009 (sec). Leaf size: 25

AsymptoticDSolveValue[(4*x^3-14*x^2-2*x)*D[y[x],{x,2}]-(6*x^2-7*x+1)*D[y[x],x]+(6*x-1)*y[x]==0,y[x],{x,0,"6"-1}]
 
\[ y(x)\to c_1 \sqrt {x} (2 x+1)+c_2 (1-x) \]